The effect of deuterated PLK1 inhibitor on its safety and efficacy in vivo - Zhang, Tingyan; Deng, Xiaobing; Jin, Haoping; Peng, Zhengshu; Hsueh, Yi-Ching; Zhang, Chunming; Niu, Gang; Yang, Jianfei (Frontiers in Oncology, 2025)
BackgroundThe FDA’s approval of deutetrabenazine, the first deuterium-labeled drug, demonstrated an improved safety profile compared to its non-deuterated counterpart, tetrabenazine. While Polo-like kinase 1 (PLK1) inhibitors have shown promise in cancer treatment, current inhibitors face challenges with toxicity and narrow therapeutic windows, highlighting the need for more effective and safer PLK inhibitors.MethodsThe molecule of PR00012 was generated by replacing all the hydrogen atoms with deuterium on piperazine of the molecule NMS-P937. Several critical in vitro assays comparing PR00012 and NMS-937 were conducted, including kinase and cellular inhibition, in vitro metabolic stability, and permeability. In vivo, both compounds were compared for their pharmacokinetics and pharmacodynamics, toxicity and efficacy.ResultsBoth compounds exhibited similar characteristics in vitro, including the inhibition of six pancreatic cancer cell lines and 416 kinases. PR00012 demonstrated a slightly longer half-life than NMS-P937 in vivo. In tumor-bearing mice, PR00012 more significantly reduced phosphorylated TCTP levels in tumors compared to NMS-P937. Importantly, animals treated with PR00012 showed lower toxicity than those treated with NMS-P937. In mice, fewer animals died from PR00012 treatment compared to NMS-P937 treatment across M-NSG, BALB/c nude, and NOD SCID strains. In a 14-day repeated administration toxicity study in Sprague-Dawley rats, one-third of rats died when treated with NMS-P937, while no rats died from PR00012 treatment. In several cell-derived xenograft (CDX) models, PR00012-treated groups consistently showed slightly better tumor growth inhibition in M-NSG, BALB/c nude, and NOD SCID mice.ConclusionThe deuterated PR00012 demonstrated an improved safety profile and slightly enhanced efficacy compared to its non-deuterated counterpart, NMS-P937. This study provides a foundation for further clinical trials investigating the treatment of various cancers.